2018
DOI: 10.1186/s12263-018-0614-6
|View full text |Cite|
|
Sign up to set email alerts
|

Biomarkers of legume intake in human intervention and observational studies: a systematic review

Abstract: There is a growing interest in assessing dietary intake more accurately across different population groups, and biomarkers have emerged as a complementary tool to replace traditional dietary assessment methods. The purpose of this study was to conduct a systematic review of the literature available and evaluate the applicability and validity of biomarkers of legume intake reported across various observational and intervention studies. A systematic search in PubMed, Scopus, and ISI Web of Knowledge identified 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 127 publications
2
39
1
Order By: Relevance
“…The fermented soymilk containing 11.69 mg genistein aglycones increased the plasma genistein with maximum concentrations of 1.02 µM (Kano et al, 2006). The soy intake was positively correlated with plasma genistein levels in different population groups (Sri et al, 2018). In our study, genistein could exert hypocholesterolemic function when the plasma concentration of genistein was up to 1.00 µM.…”
Section: Health Nutrition and Foodsupporting
confidence: 51%
“…The fermented soymilk containing 11.69 mg genistein aglycones increased the plasma genistein with maximum concentrations of 1.02 µM (Kano et al, 2006). The soy intake was positively correlated with plasma genistein levels in different population groups (Sri et al, 2018). In our study, genistein could exert hypocholesterolemic function when the plasma concentration of genistein was up to 1.00 µM.…”
Section: Health Nutrition and Foodsupporting
confidence: 51%
“…No soy products were consumed during the two studies according to the food records filled‐in by the participants. Interestingly, however, soy biomarkers related to genistein and daidzein were not observed. In Study‐V, 8‐hydroxyglycitein glucuronide shows robustness and time‐response characteristic to those of a BFI (Supporting Information S11, M6) and may be tested further for its potential application as BFI for industrially farmed animal meats, rather than general meat.…”
Section: Discussionmentioning
confidence: 92%
“…Following publication of the original article [ 1 ], the authors reported an error with the third author’s name, whereby the given name was ‘Mar Garcia’ and the family name ‘Aloy’, while the given name is in fact ‘Mar’ and the family name ‘Garcia-Aloy’.…”
Section: Correctionmentioning
confidence: 99%